Dermatillomania: In patient undergoing orthodontic treatment - Adit; Avesh Sachan; T P Chaturvedi; Rahul Agrawal; Ajit Vikram Parihar (Wolters Kluwer Medknow Publications, 2014)
Dermatillomania is a disorder in which a person habitually picks their skin, and this is a form of self-injury. It can involve any part of the body, but usually involves the face, neck, arms and shoulders. Symptoms often follow an event that has caused severe emotional distress. A dermatillomania or compulsive skin picking episode may be a conscious response to anxiety or depression but is frequently done as an unconscious habit. In this case report, a patient undergoing orthodontic treatment was found to be suffering from dermatillomania and was treated using psychological counseling.